2012
DOI: 10.1002/nem.1813
|View full text |Cite
|
Sign up to set email alerts
|

Federated management of the Future Internet: status and challenges

Abstract: SUMMARYThe Internet's original static services have been superseded by rich multimedia services with stringent end-to-end QoS requirements. Additionally, there has been a trend from simple applications offered by a single provider, towards service compositions, managed across the bounds of multiple domains. It is widely accepted that the end-to-end requirements of multimedia and composed services cannot be satisfied by the current Internet, which does not support inter-domain collaboration. The network federat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 64 publications
(109 reference statements)
0
5
0
Order By: Relevance
“…They have mentioned that shared semantics of resources, policies, and services would facilitate interoperability between the networks and provide the reuse of suitable solutions and configurations. Famaey et al [48] have reviewed the state-of-the-art research in the federated network management and concluded that one of the most important future research directions is to provide better internal semantics for the collaborative network domains. They have also emphasized the importance of having better cross-domain discovery mechanisms which can dynamically handle large amount of resource types and attributes.…”
Section: Network Managementmentioning
confidence: 99%
“…They have mentioned that shared semantics of resources, policies, and services would facilitate interoperability between the networks and provide the reuse of suitable solutions and configurations. Famaey et al [48] have reviewed the state-of-the-art research in the federated network management and concluded that one of the most important future research directions is to provide better internal semantics for the collaborative network domains. They have also emphasized the importance of having better cross-domain discovery mechanisms which can dynamically handle large amount of resource types and attributes.…”
Section: Network Managementmentioning
confidence: 99%
“…From the aforementioned description, it can be concluded that the GÉANT-NREN environment constitutes a federated environment. In the literature, there are several definitions of a federated environment [14], ranging from the 'set of domains that are governed by either a single central authority or a set of distributed collaborating governing authorities in which each domain has a set of limited powers regarding their own local interests' [15] to the 'set of independent entities or network domains that retain the responsibility over their internal management' [14]. In the first case, the participating domains concede a part of their sovereignty to the central authority or limit it themselves in the case of a distributed collaborating environment.…”
Section: Géant-national Research and Education Network Federated Envimentioning
confidence: 99%
“…Such new trends have contributed to refine the original definition of the term. Although multiple definitions exist, depending on the context in which federation is applied, there are some common key points that can be identified [10].…”
Section: Definitionmentioning
confidence: 99%
“…Federation implies a cooperation among federated components, which usually refers to the ability of federated components to leverage capabilities offered by other components in the federation. Capabilities offered depend on the specific domain and include for example infrastructure, resources (particular case for testbeds), services or applications [10]. Such sharing of capabilities is transparent from the user's point of view.…”
Section: Definitionmentioning
confidence: 99%